Do Business Growth and Technology Maximation Help SMEs Sustainability under Uncertainty? - Tai, Do Anh; Ratnawati, Ilma; Hong, Nguyen Bich (Universitas Muhammadiyah Magelang, 2024)
This research is motivated by the large number of developments in digital start-ups and large digital-based companies that are starting to understand customers. This research aims to analyze Customer Journey Mapping (CJM) and examine what instruments are involved in digital-based start-up companies to finally develop a process model for CJM in digital-based start-up businesses. This study uses the qualitative case study method on digital-based start-up companies in Magelang and Yogyakarta, Indonesia by conducting in-depth interviews with 5 start-up owners/CEOs. The results of this research show that CJM has three stages that customers will go through and the company will respond to. In the form of prepurchase, purchase, and post-purchase stages, all stages simultaneously relate to creating a unique experience. For practical implication, this model can be maximized in start-up businesses to acquire loyal customers.